New Caledonia: a Pleistocene refugium for rain forest lineages of relict angiosperms. (14th August 2015) - Pouteau, Robin; Trueba, Santiago; Feild, Taylor S.; Isnard, Sandrine
Abstract Aim In New Caledonia, relictual angiosperm lineages are over‐represented. However, the mechanisms responsible for such a distribution remain unclear. Two key hypotheses are that: (1) the diversity reflects adaptation to ultramafic substrates that ecologically filtered plant colonists; and (2) the diversity stems from wet climatic conditions that have persisted in New Caledonia during the late Quaternary while Australia and some nearby islands experienced widespread extinction events. Here, we investigate which hypothesis better explains the disharmony of relict angiosperms in New Caledonia. Location New Caledonia (South West Pacific Ocean). Methods We built species distribution models from herbarium data to determine the environmental correlates for 60 relict angiosperm taxa. Environmental variables used to characterize habitats included vegetation, substrate, and climate variables. We then tested whether the variety of xylem conduit structures borne by New Caledonian relict angiosperms, which is expected to affect plant hydraulic capacity, was correlated with habitat preference. Finally, we analysed species prevalence on different substrates and projected habitat size and distribution to the Last Glacial Maximum (LGM). Results We found a clear habitat preference among relict angiosperms for rain forests located on non‐ultramafic substrates, with the exception of taxa bearing true vessels with simple perforation plates, which harboured a wider habitat breadth. We also showed that these rain forest habitats experienced a range reduction and an eastward shift during the LGM, forming two refugial areas located on the warm and rainy east coast of Grande Terre. Main conclusions Prevalence of relict angiosperms in habitats characterized by low evaporative demand appears to be related to xylem hydraulic limitations. The disharmony of relict angiosperms in New Caledonia therefore arose from the persistence of rain forests in the island despite global fluctuations in climate during the Quaternary that affected floras in the region. Our study offers a new model to explain why certain angiosperm families are disharmonically represented in New Caledonia.